2012
DOI: 10.1002/jor.22190
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic wear debris mediated inflammatory osteolysis is mediated in part by NALP3 inflammasome activation

Abstract: Activation of myeloid cells by orthopedic particulate debris is a key event in the pathogenesis of periprosthetic osteolysis and implant loosening after total joint replacement (TJR). Several lines of evidence implicate NACHT, LRR, and PYD domains-containing protein 3 (NALP3) inflammasome-mediated production of interleukin 1 beta (IL-1b) in the pathogenesis of clinical disorders ascribable to foreign particulate materials, including asbestos, silica, and urate crystals. Recent reports indicate that orthopedic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 44 publications
3
74
1
Order By: Relevance
“…Polymethylmethacrylate particles reportedly induce a release of IL-1β in human monocytes and mouse macrophages via inflammasome activation (Burton et al, 2013). In contrast to our finding, earlier findings indicate that HEMA does not stimulate the production of IL-1β in vitro in THP-1 macrophages, human gingival fibroblasts, and keratinocytes (Rakich et al, 1999;Moharamzadeh et al, 2007).…”
Section: Discussioncontrasting
confidence: 99%
“…Polymethylmethacrylate particles reportedly induce a release of IL-1β in human monocytes and mouse macrophages via inflammasome activation (Burton et al, 2013). In contrast to our finding, earlier findings indicate that HEMA does not stimulate the production of IL-1β in vitro in THP-1 macrophages, human gingival fibroblasts, and keratinocytes (Rakich et al, 1999;Moharamzadeh et al, 2007).…”
Section: Discussioncontrasting
confidence: 99%
“…The prevalence of myeloid cell responses indicates that the NLRP3 inflammasome likely participates in prosthetic loosening, implicating crystalline particles in the pathogenesis of NLRP3-mediated diseases. Furthermore, calvarial bone resorption that is induced by polymethylmethacrylate (PMMA) particles is reduced in the absence of NLRP3 (143). The size and shape of metal alloys affect the amplitude of the inflammasome response (144).…”
Section: Figure 2 the Inflammasomes In Osteolysismentioning
confidence: 99%
“…Active Caspase-1 is required for the processing and subsequent release of active proinflammatory cytokines such as IL-1 β and IL-18 (and others) by cleaving intracellular pro-IL-1 β , pro-IL-18, and so forth into their mature forms, IL-1b and IL-18. As IL-1 β is one of the main cytokines for activation of osteolysis, an involvement in aseptic loosening is obvious, as a recent study has shown less osteolysis in caspase-1 knockout mice [68]. …”
Section: Initial Mechanisms For the Wear Particle Related Activatimentioning
confidence: 99%